2013
DOI: 10.1021/ct400706g
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chemical Space with the Alchemical Derivatives

Abstract: In this paper, we verify the usefulness of the alchemical derivatives in the prediction of chemical properties. We concentrate on the stability of the transmutation products, where the term "transmutation" means the change of the nuclear charge at an atomic site at constant number of electrons. As illustrative transmutations showing the potential of the method in exploring chemical space, we present some examples of increasing complexity starting with the deprotonation, continuing with the transmutation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 80 publications
1
61
0
Order By: Relevance
“…This would make it an alchemical derivative, which have been used to explore the energy response with respect to a change in nuclear charge in previous theoretical studies. [12][13][14][15][16][17][18] Furthermore, some early efforts to characterize the information that the h function carries, along with calculations for a couple of commonly…”
Section: Introductionmentioning
confidence: 99%
“…This would make it an alchemical derivative, which have been used to explore the energy response with respect to a change in nuclear charge in previous theoretical studies. [12][13][14][15][16][17][18] Furthermore, some early efforts to characterize the information that the h function carries, along with calculations for a couple of commonly…”
Section: Introductionmentioning
confidence: 99%
“…Second and higher order alchemical estimates were studied in Refs. [27,[47][48][49][50][51]. Insertion of µ I in Eq.…”
Section: A Theorymentioning
confidence: 99%
“…12 Alchemical transformations have been used successfully to describe the energy landscape of several molecular compounds. [13][14][15][16] Sheppard et al have shown that the alchemical potential can also be used to predict binding energies of oxygen to a Pd-Rh-Ag nanocluster from the simple calculation of a Pd nanocluster. 17,18 However, only combinations of alchemical transformations have been considered with fixed geometry before and after transformation.…”
Section: Introductionmentioning
confidence: 99%